Amide based Azodyes and their behaviour with light - Gan, Siew Mei; A. R., Yuvaraj; M. M., Yusoff; Hegde, Gurumurthy (Elsevier Publications, 2014)
The light sensitive, amide based azodyes were studied with the UV light illumination of 365 nm. Study revealed that delayed thermal back relaxation is very important for the creation of optical storage devices.It shows almost 22 seconds to convert E to Z configuration.whereas Z to E conversion takes about 6l l minutes.Presented molecule is having high potential to use in optical storage devices which needs long thermal back relaxation times.